Pengembangan Buku Ajar Sejarah Fisika Berbasis Higher Order Thingking Skill (HOTS) - I Wayan Gunada; Syahrial Ayub; Aris Doyan; Ni Nyoman Sri Putu Verawati; Hikmawati Hikmawati (Department of Physics Education, Universitas Mataram, 2021)
This study aims to develop and produce a physics history textbook based on higher order thinking skills (HOTS). This research was a development research which consists of four stages, namely: the determination stage, design, development, and dissemination. The success of the indicators of this research were seen from the feasibility of the developed textbooks. Physics history textbook based on higher order thinking skills was categorized as good and suitable for use, in terms of content, presentation, and language feasibility. Meanwhile, in terms of textbook effectiveness, it was measured by the impact of increasing students' higher order thinking skills as seen from the increase in N-gain.ÃÂ The student's high-order thinking skills had increased with N gain 0.4 (moderate category). This shows that the textbooks that have been developed are feasible and effective in terms of the ability to increase higher-order thinking skills (HOTS).